HUBUNGAN PENERAPAN MANAJEMEN TERPADU BALITA SAKIT (MTBS) DIARE DENGAN KESEMBUHAN DIARE PADA BALITA DI PUSKESMAS BAHU KOTA MANADO - Mu'is, Abdul; Ismanto, Amatus Yudi; Onibala, Franly (Universitas Sam Ratulangi, 2014)
Abstract: Integrated Management of Childhood Illness (IMCI) is an integrated management approach/integrated management of sick children who come in health care, either about some classifications of disease, nutritional status, immunization status and treatment of the sick children and counseling. According to the 2005 WHO has recognized that the IMCI approach are complete to anticipate the diseases that often lead to death in children under five in the world, including diarrhea. This type of research used was descriptive cross-sectional approach with analytic. Sampling technique used was accidental sampling. The sample in this study consisted of 34 peoples. Results of Chi-Square test statistic values obtained Ï = 0.000. This means that the Ï-value is smaller than Î± (0.05). It can be concluded that there is a relationship between the implementation of integrated management of sick children (IMCI) diarrhea to cure diarrhea in infants in PHC Bahu at Manado City. Recommendations are expected for the existing services, especially in Bahuâ€™s health centers can improve the application of IMCI complete with participated in IMCI training. Keywords: IMCI, Diarrhea, Toddler. Abstrak: Manajemen Terpadu Balita Sakit (MTBS) adalah suatu manajemen melalui pendekatan terintegrasi/terpadu dalam tatalaksana balita sakit yang datang di pelayanan kesehatan, baik mengenai beberapa klasifikasi penyakit, status gizi, status imunisasi maupun penanganan balita sakit tersebut dan konseling yang diberikan. Menurut WHO tahun 2005 telah mengakui bahwa pendekatan MTBS tergolong lengkap untuk mengantisi pasipenyakit-penyakit yang sering menyebabkan kematian pada balita di dunia, termasuk diare. Jenis penelitian yang digunakan ialah pendekatan cross sectional dengan descriptive analitik. Tehnik pengambilan sampel yang dipakai ialah aksidental sampling. Sampel dalam penelitian sebanyak 34 orang. Hasil uji statistik Chi-berarti nilai p lebih kecil dari Î± (0,05). Dapat disimpulkan bahwa ada hubungan antara penerapan manajemen terpadu balita sakit (MTBS) diare dengan kesembuhan diare pada balita di Puskesmas Bahu Kota Manado. Saran diharapkan bagi pelayanan terutama yang ada di Puskesmas Bahu dapat meningkatkan Penerapan MTBS yang lengkap dengan mengikuti pelatihan MTBS. Kata Kunci: MTBS, Diare, Balita.